A structure–property study of fluoranthene-cored hole-transporting materials enables 19.3% efficiency in dopant-free perovskite solar cells. Issue 28 (14th June 2019) - Sun, Xianglang; Wu, Fei; Zhong, Cheng; Zhu, Linna; Li, Zhong'an
Abstract : A systematic structure–property correlation study was conducted to preliminarily elucidate an inherent regularity governing the structure of dopant-free HTMs. Abstract : To date, most of the prevailing organic hole-transporting materials (HTMs) used in perovskite solar cells (PVSCs), such as spiro-OMeTAD and PTAA, generally require a sophisticated doping process to ensure their reasonable hole-transporting properties. Unfortunately, the employed dopants/additives and the associated oxidation reactions have been shown to deteriorate the long-term device stability seriously. The exploitation of efficient and stable dopant-free HTMs is thus strongly desired for PVSCs. However, effective molecular design strategies for dopant-free HTMs are still lacking. Thus far, only a few of them yielded comparable performance to their doped counterparts, while their synthetic costs are still high. In this work, a new class of cost-effective small molecule dopant-free HTMs have been developed using readily available fluoranthene as the structural framework. The structure–property correlation of the fluoranthene-based HTMs was carefully investigated by tuning their structural geometry (linear vs. branched), connection between electron-donating and electron-withdrawing moieties (single bond vs. ethylene), and the substitution position of the methoxy side-groups ( para - vs. meta -). As a result, the optimized molecule, FBA3, was demonstrated to serve as an efficient dopant-free HTM in a conventional PVSC to deliver an impressive power conversion efficiency of 19.27%, representing one of the best cost-effective dopant-free organic HTMs reported thus far.